Development of a fluorescence-linked immunosorbent assay for detection of avermectins using a fluorescent single-domain antibody1. Issue 9 (7th May 2015) - Chen, Min; Ding, Shuangyang; Wen, Kai; Xie, Sanlei; Wang, Qi; Pei, Xingyao; Xie, Jie; Wang, Zhanhui; Jiang, Haiyang
<x xml:space="preserve">Abstract</x> A schematic diagram of the FLISA based on a fluobody for the determination of AVMs. Note: FLISA, fluorescence-linked immunosorbent assay; GFP, green fluorescent protein; fluobody, fluorescent single-domain antibody; ABM, abamectin; OVA, ovalbumin; and AVMs, avermectins.